La Confession et le Texte licencieux Pratiques textuelles et éditoriales dans l'Europe du XVIIIe siècle - Meise, Helga; Haquette, Jean-Louis (EPURE, Éditions et presses universitaires de Reims, 2020)
The present volume examines, from a comparative perspective, the textual practices of confession that characterise a number of eighteenth-century libertine, licentious and pornographic texts published in England, Holland, France and the German-speaking countries. This type of enunciation, in the context of a printed publication, is based on a tension between sexual intimacy and collective dissemination through the book: this exhibition of intimacy is constitutive of the pleasure aimed at by this type of text, but it obviously encounters the social norms of literary representation. Sometimes repressed, often tolerated, this literature has a wide European circulation. Three aspects are highlighted: the role that the texts reserve for confession, the impact of control practices by the public authorities, and the reception and circulation of the texts among the readership.